Improving fatigue properties of normal direction ultrasonic vibration assisted face grinding Inconel 718 by regulating machined surface integrity - Nianwei Xu; Renke Kang; Bi Zhang; Yuan Zhang; Chenxu Wang; Yan Bao; Zhigang Dong (International Journal of Extreme Manufacturing, 2024)
Fatigue properties are crucial for critical aero-engine components in extreme service environments, which are significantly affected by surface integrity (SI) indexes (especially surface topography, residual stress σ _res , and microhardness) after machining processes. Normal-direction ultrasonic vibration-assisted face grinding (ND-UVAFG) has advantages in improving the machinability of Inconel 718, but there is a competitive relationship between higher compressive σ _res and higher surface roughness R _a in affecting fatigue strength. The lack of a quantitative relationship between multiple SI indexes and fatigue strength makes the indeterminacy of a regulatory strategy for improving fatigue properties. In this work, a model of fatigue strength ( σ _f ) _sur considering multiple SI indexes was developed. Then, high-cycle fatigue tests were carried out on Inconel 718 samples with different SI characteristics, and the influence of ND-UVAFG process parameters on SI was analyzed. Based on SI indexes data, the ( σ _f ) _sur distribution in the grinding surface layer for ND-UVAFG Inconel 718 samples was determined using the developed model, and then the fatigue crack initiation (FCI) sites were further predicted. The predicted FCI sites corresponded well with the experimental results, thereby verifying this model. A strategy for improving the fatigue life was proposed in this work, which was to transfer the fatigue source from the machined surface to the bulk material by controlling the SI indexes. Finally, a critical condition of SI indexes that FCI sites appeared on the surface or in bulk material was given by fitting the predicted results. According to the critical condition, an SI field where FCI sites appeared in the bulk material could be obtained. In this field, the fatigue life of Inconel 718 samples could be improved by approximately 140%.